An exploration of strong opioid utilisation in non-cancer pain patients in UK primary care, 2000-2010 - Adan Hag Hersi, Muna (2018)
Background Opioids are the most potent analgesics available and their treatment is well established in cancer and acute pain. However, their long-term use in non-cancer pain is worrisome due to insufficient evidence on long-term effectiveness and safety. Population-based research examining the utilisation of opioids in non-cancer pain patients in UK primary care remains limited and little information exists on patients receiving long-term therapy.